Due Diligence Procedures and Principles for Financial Analysis and Corporate Governance - Grove, Hugh; Clouse, Mac (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2018)
An initial set of seven procedures is developed for assessing a company’s common stock. A second set of ten procedures is developed for performing stealth or external financial (forensic) analysis on a company’s common stock. Also, a set of eight corporate governance principles, developed in secret over one year by 13 prominent CEOs of U.S. based, global companies, are elaborated for analyzing a company’s corporate governance practices in this paper. The purpose of this paper is to portray how these procedures and principles can be used by financial analysts and Boards of Directors in helping to assess the viability of the companies they are analyzing or serving and to develop key questions to ask of corporate executives. Thus, the first set of procedures elaborates seven reasons to consider in assessing a company’s stock. The second set of procedures develops ten steps of stealth forensics to investigate the possibility of financial shenanigans or fraud by a company. The last set of eight principles assesses the strength of corporate governance in a company. The importance of these principles is demonstrated by matching them with the practices of just 18 mainly global companies that managed to destroy 1.5 trillion of market capitalization. All these twenty-five procedures and principles will help strengthen financial analysis and corporate governance, especially for the role of financial analysts and Boards of Directors in assessing the value of companies’ common stock for investors.